PERBEDAAN KINERJA KONSELOR SMK NEGERI DAN SMK SWASTA KOTA PEKALONGAN - Yusrina, Putriani (Indonesian Journal of Guidance and Counseling: Theory and Application, 2012)
This study have to know of difference in performance between the counselor’s SMK state and the counselor SMK private Pekalongan city. In this study population was all counselors in school state and the counselor school private Pekalongan city with a number of  32 counselors. The research sample using sampling purporsive 13 counselors SMK state and 17 counselors SMK private. Retrieval of data in this study using a questionnaire. The method of data analysis using different test (t-test). The difference between the performance of counselors and vocational Private SMK known that the t value 2.775 and t tables with 5% is 2.042 so t value > t table then the result is a significant difference between the performance counselor SMK state with performance counselor of State Private